The The Meaning of Indonesian Culture in the Vocabulary of Indonesian Language Textbooks for Japanese Speakers - Fauzah, Nunik Nur Rahmi; Hidayati, Yanti (English Literature Department, Faculty of Economics, Law, and Humanities, 2023)
The aim of this research is to describe the lexical and cultural meanings, as well as the functions of cultural vocabulary in Indonesian language textbooks for Japanese learners. The research employs an ethnolinguistic approach and utilizes a descriptive method. Data is collected through observation and note-taking techniques. The data sources include the books Yasashii shoho no Indonesia Go,Nichijou Indonesia Go Kaiwa Neitibu Hyougen, and Kaisoku Masutaa Indonesia Go. The data under consideration consists of cultural vocabulary. Ten cultural vocabulary terms were identified: koucha, yakitori, rebaran, oukyuu, borobudu-ru jiin, gado gado, chanan, gamuran, and sarun. The cultural meanings derived from these vocabulary terms encompass etiquette and familiarity, mutual respect in diversity, forgiveness, and social bonds, orderliness, conceptualization, and structure, religiosity, environmental appreciation, artistic passion, tolerance, cooperation, simplicity, and courtesy. In terms of functionality, some lexicons undergo functional changes, while others remain unchanged. Lexicons such as koucha, yakitori, gado gado, gamuran, kubaya, and sarun experience functional changes, whereas rebaran, oukyuu, Borobudu-ru jiin, and chanan remain unchanged.